Mitigating Aquifer Crisis in Indonesia's New Capital, Nusantara: Problems and Lessons Learned from Singapore - Rahmawan, Ardianto Budi; Eliana, Gabriela (Közigazgatási és Infokommunikációs Jogi PhD Tanulmányok, 2023)
Water availability is crucial to every nation’s capital. The appointment of Indonesia’s new capital through Indonesian Law No. 3 Year 2022 poses concerns regarding aquifer crisis as Nusantara is located on top of medium- to low-productivity aquifers. The shift of capital would entail groundwater resources utilization, which pose huge aquifer crisis risks. In contrast, Singapore, a city-state with limited aquifers, sufficiently mitigated aquifer crisis due to its water management policy that could accommodate its citizens’ water demands. In this paper, the authors conducted a comparative analysis on Singapore’s water management policies to provide recommendations on the shift of Indonesia’s capital to fulfill water demands and mitigate aquifer crisis. Using a normative approach, this paper portrays the lessons that can be taken from Singapore in ensuring water availability amidst its limited water resources and high demand of water.